Elaboración de un curso virtual en la plataforma moodle, del libro Kichwa Rimay: aprenda el kichwa inicial en cuatro lunas del autor Ángel Polivio Chalan Chalan, Loja, periodo 2014- 2015 - Sarango Salvay, Andrés Patricio (2016)
The present research work, the lack of knowledge of teachers in the use of ICT in the teaching-learning process, the use of traditional resources such as slate, the textbook in teaching Kichwa language, producing monotonous teaching and not awaken interest in students to learn. Based on these needs the following research work was entitled: "Development of an online course in Moodle Book Kichwa rimay: learn the initial four moons Kichwa author Polivio Chalan Angel Loja period 2014- 2015" The ADDIE methodology was used to preparation of the thesis, which allowed to analyze, design, develop, implement and evaluate the virtual course, it was developed in the virtual platform Moodle using tools like EdiLim, Camtasia and Microsoft Office package for activities, resulting in a virtual course technology meets excellent didactic teaching aspects, according the record of assessment applied to students. In conclusion the incorporation of essential Virtual Course as a teaching tools that allowed follow the content, objectives and raised curricular skills, while support the teaching-learning process, it provides that students obtain optimal learning; Therefore teachers and education authorities are recommended to implement virtual course to improve teaching-learning process